2017
DOI: 10.1200/cci.17.00015
|View full text |Cite
|
Sign up to set email alerts
|

Bidirectional Text Messaging to Monitor Endocrine Therapy Adherence and Patient-Reported Outcomes in Breast Cancer

Abstract: Introduction Up to 40% of patients with breast cancer may not adhere to adjuvant endocrine therapy. Therapy-related adverse effects (AEs) are important contributors to nonadherence. We developed a bidirectional text-message application, BETA-Text, that simultaneously tracks adherence, records symptoms, and alerts the clinical team. Patients and Methods We piloted our intervention in 100 patients. The intervention consisted of text messages to which patients responded for 3 months: daily, evaluating adherence; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
58
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(60 citation statements)
references
References 33 publications
2
58
0
Order By: Relevance
“…We demonstrate that social media can be effective in rapidly obtaining large numbers of patient responses regarding care issues. Similar to previous studies [1,7,10,[17][18][19][34][35][36][37][38][39], our results demonstrate that most patients (91%) who take ET experience related side effects, and one-third discontinue treatment early. Our findings suggest that online patient communities can be a valuable tool for identifying variables that influence breast cancer patients' adherence to ET.…”
Section: Discussionsupporting
confidence: 90%
“…We demonstrate that social media can be effective in rapidly obtaining large numbers of patient responses regarding care issues. Similar to previous studies [1,7,10,[17][18][19][34][35][36][37][38][39], our results demonstrate that most patients (91%) who take ET experience related side effects, and one-third discontinue treatment early. Our findings suggest that online patient communities can be a valuable tool for identifying variables that influence breast cancer patients' adherence to ET.…”
Section: Discussionsupporting
confidence: 90%
“…Our study supports previous studies which showed that SMS messaging could improve treatment adherence and was acceptable to participants [ 16 , 19 , 27 ]. Despite concerns about long-term attrition in previous studies [ 28 ], the MPAS results showed that even with a decrease in response rates over time, the response rates were consistently higher than the PEDC rates over the same period, possibly because of better engagement among the users.…”
Section: Discussionsupporting
confidence: 91%
“…endpoints (Job, Spark, Fjeldsoe, Eakin, & Reeves, 2017;Mougalian et al, 2017), providing support that these programs may be beneficial long-term. Long term (12-24 month) randomised controlled trials are needed to provide evidence of continued participant engagement and benefit.…”
Section: Methodsmentioning
confidence: 91%